3D photothermal imaging of subsurface defects in composite materials. (September 2021) - Thummerer, G.; Mayr, G.; Burgholzer, P.
Abstract: In this work, we show the application of the virtual wave concept for 3D "pulse-echo" photothermal defect imaging in anisotropic materials. We consider a woven and a unidirectional carbon fiber reinforced material including flat bottom holes with varying diameter-to-depth ratios. We discuss the characteristics of the virtual wave signal due to disturbed heat diffusion caused by a defect and the resulting consequences for our defect reconstruction method regarding the incorporation of prior information. In addition, we optimize the virtual wave concept in terms of computation time by performing a parameter study and a physical-based derivation that suggest reasonable values for the temporal and spatial discretization, respectively. The paper presents a very fast, easily interpretable and efficient 3D reconstruction tool for active thermography testing of anisotropic materials.